Buffer zone concept and its potential implementation in Tasek Bera / Che Bon Ahmad, Jamalunlaili Abdullah and Jasmee Jaafar - Ahmad, Che Bon; Abdullah, Jamalunlaili; Jaafar, Jasmee (Universiti Teknologi MARA Cawangan Selangor, 2018)
Tasek Bera (TB), one of the Protected Areas (PA) in Malaysia is an important site for natural ecosystem and community’s life. Previous studies suggested that the activities around the Pas gave a great impact to the latter. Thus, the implementation and management of the surrounding areas – Buffer Zones (BZ) are necessary to safeguard the PAs. This study interviewed in- depth, six stakeholders of TB and the adjacent areas. Results indicated that although all stakeholders agreed on the overall concept and the importance of the BZs, there are disagreement in term of threats and opportunities derived from the potential implementation of it.